2010
DOI: 10.1080/10790268.2010.11689720
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Myelomeningocele: Anthropometric Measures

Abstract: Objective: To evaluate the appropriate use of arm span measurements as a substitute for height/linear length to evaluate obesity in people with myelomeningocele by comparing calculated body mass indices (BMIs) with recently published BMI graphs by the Centers for Disease Control and Prevention (CDC) and National Center for Health Statistics standards (NCHS) published in 2000. Study Design: Retrospective analysis of collected data on patients seen in the University of Washington Birth Defects Clinic from July 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Half (52-68%) have had a romantic relationship 131, although this rate is lower than in typically developing young adults 164, 169. The lowest level of life satisfaction is in the areas of romantic relationships, employment, and financial independence 131.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Half (52-68%) have had a romantic relationship 131, although this rate is lower than in typically developing young adults 164, 169. The lowest level of life satisfaction is in the areas of romantic relationships, employment, and financial independence 131.…”
Section: Quality Of Lifementioning
confidence: 99%
“…9 Several studies have analyzed the use of more adequate cut-off points and different measures 5 with varying results. One of the nutritional challenges seen in patients with myelomeningocele is detecting the most adequate indicator to diagnose obesity.…”
Section: Original Articlementioning
confidence: 99%
“…11 Body mass index (BMI) can be difficult to evaluate in patients with MMC because of the scoliosis, the presence of contracture in the lower extremities and their altered dimensions and growth delay. 38,39 Previous studies from general paediatric populations have reported that maternal dietary folate intake during pregnancy positively correlates with BMD of the child. 40 …”
Section: Environmental Factorsmentioning
confidence: 99%